Prōï̀ énnycha lían anastàs exē͂lthen (Mark 1,35; 16,2.9a) - Andrejevs, Olegs (Revue biblique, 2025)
Since at least the 1960s, a number of scholars have proposed the existence of an intentional link between Mark 1,35 and 16,1-8, including as recently as 2006 (M.E. Boring). Others have expressed skepticism, with clearly articulated objections coming from R.H. Gundry in 1993. In his analysis, Boring has not responded to Gundry’s observations. How valid are the objections that have been raised against this hypothesis? In this study, Mark 1,35 is examined from three perspectives. First, surveying the last century of scholarship, it is assessed whether Mark 1,35 is more likely to be traditional or redactional. Second, Mark’s use of the term πρωΐ, denoting the fourth night watch in 13,35 and refined in the gospel only in 1,35 (πρωῒ ἔννυχα λίαν) and 16,2 (λίαν πρωΐ), receives close attention. Finally, Mark 1,35 is examined through the lens of classical narratology. The conclusion reached is that Mark 1,35 is likely a redactional creation of the evangelist, exclusively shares with 16,2 the context of the early portion of the fourth night watch on the first day of the week, and is likely to be intended as a proleptic foreshadowing of the resurrection of Jesus.